ROLE OF ISLAM IN MALAYSIA’S PUBLIC DIPLOMACY: ABDULLAH BADAWI ADMINISTRATIONS - Nur Fareha (International Journal of Law Reconstruction, 2018)
This paper investigates the role of Islam in Malaysia’s as a reform on soft power tools under the leaderships of Malaysia’s fifth Prime Minister, Tun Abdullah Badawi. The study emphasis the reform in policy making, philosophies and approaches of the premiers in developing an understanding of the importance of Islam’s role in Malaysia’s public diplomacy. The research also determines the influence of international events in the public diplomacy policies. The study takes a constructivist approach and includes faith diplomacy into the realm of public diplomacy. This study has achieved its objective of understanding Islamic public diplomacy in Malaysia’s administration and should be useful for developing future policies of public diplomacy for domestic and international consumption. It is an interesting reflection of this study that the common perception that Abdullah’s public diplomacy was not successful is incorrect; this perception is founded on the labelling that Abdullah’s version carried, which is because Abdullah, true to his character and personality, embraced and enriched previous premiership Islamization principles, without wanting to change them. Though there are arguments as discussed that Islam Hadhari declined, it only declined in the domestic context. In the international arena it appealed to a much wider audience.